The Effect of Active Paper Packaging Enriched with Oleoresin from Solid Waste of Pressed Curcuma xanthorrhiza Roxb. Placement Methods on Quality of Refrigerated Strawberry (Fragaria x ananassa) - Rohula Utami; Kawiji Kawiji; Windi Atmaka; Lulus Nurmaya; Lia Umi Khasanah; Godras Jati Manuhara (Universitas Sebelas Maret, 2021)
Strawberry is a popular and nutritious fruit. However, its improper post-harvest handling leads to quality degradation. The aim of this study was to investigate the effects of active paper packaging placements methods on strawberry (Fragaria x ananassa) quality during refrigerated storage. Strawberry quality was determined based on the physical (weight loss, hardness, color), chemical (pH, total titratable acid, total soluble solids and vitamin C content) and microbiological (total plate count) properties. The results of this study indicated that different placement methods of active paper packaging had no significant effect on the physical and chemical qualities; but it did affect the microbiological quality of the strawberries. At the end of the experiment (12 days), the microbial content of C (the bottom and walls), D (covering all surfaces) and E (cut into pieces) samples were significantly lower than the A (without active paper packaging) and B (the bottom) samples. The Total Plate Count (TPC) values of the control and B samples were higher than the maximum acceptable limit of 6 log10 colony-forming units (CFU) g-1, while the other samples remained below the limit. These results indicated that a larger surface area of active paper that had contact with the strawberries provided better protection against microbes. Due to their microbial properties, C, D and E treatments maintained the strawberry quality for up to 12 days, compared with 9 days for control and B treatments. Active paper packaging containing oleoresin from solid waste of pressed Curcuma xanthorrhiza Roxb. can be applied to extend the shelf life of strawberries during refrigerated storage.